Hybrid design method for wind-adaptive architecture. (December 2019) - Kabošová, Lenka; Foged, Isak; Kmeť, Stanislav; Katunský, Dušan
The linkage of individual design skills and computer-based capabilities in the design process offers yet unexplored environment-adaptive architectural solutions. The conventional perception of architecture is changing, creating a space for reconfigurable, "living" buildings responding, for instance, to climatic influences. Integrating the element of wind to the architectural morphogenesis process can lead toward wind-adaptive designs that in turn can enhance the wind microclimate in their vicinity. Geometric relations coupled with material properties enable to create a tensegrity-membrane structural element, bending in the wind. First, the properties of such elements are investigated by a hybrid method, that is, computer simulations are coupled with physical prototyping. Second, the system is applied to basic-geometry building envelopes and investigated using computational fluid dynamics simulations. Third, the findings are transmitted to a case study design of a streamlined building envelope. The results suggest that a wind-adaptive building envelope plays a great role in reducing the surface wind suction and enhancing the wind microclimate.